Rhino Cerebral Mucormycosis with Post Surgical Complications in Diabetes: A Case Report (Anwer Khan Modern Medical College Journal, 2017)
Rhinocerebral mucormycosis is a rare life-threatening infection caused by fungi from the order Mucorales. The disease occurs mostly in association with diabetic ketoacidosis. Because of its rapid progression and high mortality, early recognition and aggressive treatment offer the only chance to increase the survival rate. A case of rhinocerebral mucormycosis in a diabetic male patient presenting as post surgical complication is reported. The clincal manifestations, diagnosis, and treatment of rhinocerebral mucormycosis are discussed.Anwer Khan Modern Medical College Journal Vol. 7, No. 2: Jul 2016, P 56-62